Ecocritical Reading in the Qur’an: An Analysis of the Concept of Corruption and Its Ecological Ethical Implications - Muhammad Amirul Huda; Abdul Mufid; Naila Intania (QOF, 2026)
This study examines the meaning structure and ecological ethical implications of fasād in QS. al-Rūm [30]:41 and QS. al-Baqarah [2]:205 through a qualitative textual approach that combines thematic interpretation and ecocritical reading. The analysis focuses on the lexical and exegetical meanings of fasād, the subject of responsibility, the object of destruction, the spatial scope of damage, and the relation between human conduct and its consequences. The study finds that QS. al-Rūm [30]:41 presents fasād as a visible consequence of collective human action in the domains of land and sea, while QS. al-Baqarah [2]:205 presents fasād through the destructive conduct of a particular actor who damages crops and the continuity of life. These differences indicate distinct textual emphases between collective ecological consequence and actor-centered destructive action, without implying that the Qur'an constructs rigid ecological models. Based on these findings, this study formulates three analytical orientations for Qur'anic ecocritical reading: ecological relationality, the manifestation of ecological consequence within creation, and theological responsibility. This framework does not attribute autonomous agency to nature or impose modern ecological theory upon the Qur'anic text. It uses ecocritical sensitivity under the semantic and theological control of tafsīr. The study contributes to Qur'anic ecological discourse by clarifying how ecological ethics can be derived from textual indications of fasād while acknowledging the epistemological limits of applying ecocriticism to revelatory texts.